Law Enforcement Against Illegal Logging in The Jurisdiction of the Tejakula Buleleng Police Sector - Sudiarta, I Nyoman (International Journal of Contemporary Sciences (IJCS), 2024)
The practice of illegal logging is generally carried out by individuals who have official permission from the government to carry out forest logging, such as holders of Forest Ruler Rights (HPH) concession permits, however, if it is further detailed, the perpetrators of illegal logging are organized groups. Law enforcement in overcoming the crime of illegal logging Tejakula Sector Police use 2 (two) means, namely: Penal efforts that focus more on the repressive nature, namely actions taken after the crime occurs with law enforcement and imposition of penalties for crimes that have been committed, and non-penal efforts, a countermeasure that focuses more on the preventive nature, namely actions in the form of prevention before the crime occurs. To solve the problems in this study, the research method is the type of normative legal research supported by conducting field observations with the interview process with the Tejakula Buleleng Sector Police Investigator. So the expected results in this study, the most substantial is the difference in interpretation in terms of administrative sanctions there is a blurring of legal norms in Article 18 paragraph (1) of Law Number 18 of 2013 concerning the prevention and eradication of forest destruction, because in its application or implementation sometimes there is overlap between the meaning of the sentence of the implementation of government coercion sanctions with administrative sanctions of forced money